Effect of water stress in maize crop production and nitrogen fertilizer fate - Rimski Korsakov, Helena (2009)
Maize production is affected by water and nitrogen (N) deficit either separately or joined, but this fact is not completely defined. The aim was to evaluate the fate of N in maize fertilized and subjected to water stress in controlled conditions. A greenhouse experiment was carried out at the University of Buenos Aires campus. The design was a 2 × 2 factorial with four replications. The factors were N: 70 and 140 kg N ha-1 as labeled urea (15N), and water: 100% or 50% of the potential evapotranspiration. The harvest of aerial and root biomass was carried out at R1 stage. Nitrogen in plants, soils nitrate, ammonia volatilization, and 15N percentage were determined. Obtained results only partially agree with previous research. Water stress depressed aerial biomass production independently of N doses. When water was limiting, the uptake of N from fertilizer was independent of N. When water was not limiting, N uptake increased with the higher N doses. Volatilization losses were 3.7 to 7.8% of N applied as fertilizer. Plant N recovers was around 45% of the N applied, except in treatment water stressed with high N rate (19%). Nitrate-N from the fertilizer in the soil at harvest and accumulated N from the fertilizer in plant were lineally related (r2 = 0.54; p < 0.001). Important destinations of N were accumulation in plant, volatilization and incorporation into soil organic matter. However, residual nitrate was a main fate in heavily fertilized and water deficit treatment. This process could lead to the eventual nitrate leaching. Copyright © Taylor & Francis Group, LLC.